Albumin to Total Cholesterol Ratio and Mortality in Peritoneal Dialysis - Wu, Xianfeng; Meng, Jiao; Zhou, Lei; Zhan, Xiaojiang; Wen, Yueqiang; Wang, Xiaoyang; Feng, Xiaoran; Wang, Niansong; Peng, Fenfen; Wu, Junnan (Frontiers in Medicine, 2022)
Background: Serum albumin and total cholesterol are associated with mortality. In clinical practice, evaluating the association of combining album and total cholesterol with mortality may be more reasonable. Thus, we examined the association between serum albumin to total cholesterol ratio and mortality in peritoneal dialysis (PD) patients. Methods: We conducted a retrospective cohort study of 3447 incident CAPD patients from five PD centers in China from January 1, 2005, and May 31, 2020. The association between albumin to total cholesterol ratio and mortality was evaluated. Results: With a median follow-up of 39.3 months, 762 (22.1%) all-cause deaths occurred, including 382 (11.1%) cardiovascular deaths. As compared with a serum albumin to total cholesterol ratio of 0.77 to 0.82 (reference range), a higher ratio (> 0.82) was associated with increased risks of all-cause mortality (hazards ratio [HR], 1.54; 95% confidence interval [CI], 1.16 to 2.05, E-value = 2.45) and cardiovascular mortality (HR, 2.10; 95% CI, 1.35 to 3.29, E-value = 3.62). A lower ratio (< 0.77) was also associated with increased risks of all-cause mortality (HR, 1.46; 95% CI, 1.10 to 1.94, E-value = 2.28) and cardiovascular mortality (HR, 1.78; 95% CI, 1.14 to 2.78, E-value = 2.96) compared with the reference. No interaction was observed in subgroup analyses of age, sex, diabetes mellitus, hypertension, prior cardiovascular disease, and hyperlipidemia, and malnutrition (serum albumin < 3.6 g/dL). Conclusions: An albumin to total cholesterol ratio before the start of PD between 0.77 and 0.82 was associated with a lower risk of death than a higher or lower ratio, resulting in a U-curve association. Therefore, serum albumin to total cholesterol ratio, as an inexpensive and readily available biochemical biomarker, may further improve the stratification risk of mortality in PD patients.